Zn Doped NiMn-Layered Double Hydroxide for High Performance Ni–Zn Battery. Issue 16 (29th December 2020) - Wang, Shiyuan; Duan, Xinxuan; Gao, Tengfei; Wang, Zhaolei; Zhou, Daojin; Sun, Kai; Shang, Zhicheng; Kuang, Yun; Tian, Shubo; Li, Xuejin; Liu, Wen; Sun, Xiaoming
Abstract : Rechargeable Ni–Zn battery with aqueous alkaline electrolyte represents a low-cost, safe and environmentally benign battery technology but limited in energy density and inferior cycling stability. Herein, Zn doped NiMn-layered double hydroxides have been proposed to enhance the specific capacity and cycle stability of Ni–Zn battery, which featuring lower Ni valence state and flower-like micro-structure. As a result, NiMn-LDH with 5 at% Zinc doping in can achieve a high mass-specific capacity of 294 mAh g −1 at 1 A g −1 and enhanced stability, manifesting one of the best cathode materials for Ni–Zn batteries. Moreover, the corresponding Ni–Zn battery behaves a high capacity of 180 mAh g −1 at 1 A g −1 and 100% retention after 1000 cycles. This work demonstrates the superiority of materials design in both elemental composition and hierarchical structure to achieve high performance in energy storage, which can be also adapted to other battery systems.